Síntese de catalisadores utilizando garrafa pet para a produção de biodiesel. - Souza, Juliana Kelly Dionízio de (2012)
The heterogeneous catalysis is a promising alternative to solve the environmental problems found in homogeneous catalysis, because it allows the continuous use of the catalyst until its deactivation and minimizes the generation of effluents. Thus, this work aims to synthesize, optimize and evaluate the activity of heterogeneous catalysts, using PET bottles as a starting material in the synthesis of the active phase and SiO2 as catalyst support for the transesterification reaction of soybean oil. The the catalysts were obtained by a impregnating reaction using methanol. The active phase, the catalysts and catalyst support were characterized by X-ray diffraction (XRD), infrared (IR), Raman spectroscopy, scanning electron microscopy (SEM) and EDS, thermal analysis (TG) and measurement surface area (BET). The biodiesels has been synthesized using a molar ratio of 1:9 (soybean oil: methanol), 0,1 g of active phase as catalyst (room temperature) and 1,2 g of the catalysts synthesized at 75 °C, where its kinematic viscosities were measurements. All catalysts were effective in the synthesis of biodiesel because the viscosity reduction of soybean oil used was very significant, indicating that may have occurred the transesterification process, among all biodiesels synthesized the catalyst that stood out was the 30%-K2CO3/70% SiO2, which was obtained greater viscosity reduction at a lower reaction time. The quality tests were made for 1h Bio-30%, which proved be inside the parameters established by the Agência Nacional de Patróleo (ANP). The experiment reuse of the catalyst used in the synthesis of Bio-1h 30%, showed that the catalytic activity is reduced due to possible leaching phenomenon, then preliminary studies have been proposed to study the possible leaching of the active phase.